Analisis SWOT Dalam Penentuan Strategi Bisnis Kalisani Coffee Shop - Fakhri Fakhri; Deni Kusuma; Juliana Angelica De Sena; Leonardo Maulana (Pusat Riset dan Inovasi Nasional, 2023)
Kalisani Coffee Shop is a cafe business located in the Andalas University (UNAND) campus environment. In this context, this study aims to conduct a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) of the Kalisani Coffee Shop UNAND and formulate a business strategy in accordance with the SWOT findings. The method used in this research is a case study by collecting data through observation, interviews, and document analysis. SWOT analysis was conducted to identify internal and external factors that affect the business performance of Kalisani Coffee Shop UNAND. The results of the SWOT analysis show that some of the strengths of the Kalisani Coffee Shop UNAND are a strategic location on campus, good quality coffee products, and support from the student community. However, there are some weaknesses (weaknesses) such as lack of menu variety and lack of effective promotion. In terms of opportunities, Kalisani Coffee Shop UNAND can take advantage of the increasing public interest in coffee and the increasing number of students at UNAND. Meanwhile, several threats faced by Kalisani Coffee Shop UNAND are intense competition from similar cafes and fluctuations in raw material prices. Based on the findings of the SWOT analysis, several business strategies are recommended for Kalisani Coffee Shop UNAND. These strategies include increasing menu variety by adding snacks and non-coffee drinks, increasing promotions through social media and collaboration with the student community, as well as improving the quality of customer service. In addition, Kalisani Coffee Shop UNAND can also establish partnerships with local suppliers to obtain quality raw materials at more stable prices. The method that can be used to implement this business strategy is the stakeholder mapping method to identify groups that are has an interest in Kalisani Coffee Shop UNAND, and a cost-benefit analysis method to evaluate the potential benefits and costs associated with implementing these business strategies.